Trends in quality-adjusted skill premia in the United States, 1960 - 2000 - Pedro Carneiro; Sokbae Lee (Centre for Microdata Methods and Practice (cemmap), 2008)
This paper presents new evidence that increases in college enrollment lead to a decline in the average quality of college graduates between 1960 and 2000, resulting in a decrease of 8 percentage points in the college premium. The standard demand and supply framework (Katz and Murphy, 1992, Card and Lemieux, 2001) can qualitatively account for the trend in the college and age premia over this period, but the quantitative adjustments that need to be made to account for changes in quality are substantial. Furthermore, the standard interpretation of the supply effect can be misleading if the quality of college workers is not controlled for. To illustrate the importance of these adjustments, we reanalyze the problem studied in Card and Lemieux (2001), who observe that the rise in the college premium in the 1980s occurred mainly for young workers, and attribute this to the differential behavior of the supply of skill between the young and the old. Our results show that changes in quality are as important as changes in prices to explain the phenomenon they document.
Keywords: 330; Bildungsverhalten; Bildungsniveau; Akademiker; Bildungsertrag; Lohn; USA